2021
DOI: 10.3390/ijerph18084122
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Oncological Care during the SARS-CoV-2 Virus Pandemic

Abstract: Recently, the outbreak of the SARS-CoV-2 virus and the COVID-19 pandemic significantly affected the health situation of the entire society and necessitated reorganization of health care including oncology. The objective of this study was to examine the perception of medical services by cancer patients during the pandemic and to identify the key elements influencing the level of satisfaction with oncological care. Of note, 394 patients diagnosed with cancer treated in inpatient oncology wards participated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“… 43 Still, a study that sought the satisfaction of hospitalized patients showed the interpersonal skills of doctors and nurses as lower patient satisfaction ratings. 19 However, in a study, it was stated that the care experience was identical when compared with the service before the pandemic. 44 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 Still, a study that sought the satisfaction of hospitalized patients showed the interpersonal skills of doctors and nurses as lower patient satisfaction ratings. 19 However, in a study, it was stated that the care experience was identical when compared with the service before the pandemic. 44 …”
Section: Resultsmentioning
confidence: 99%
“… 34 It was also observed in one study with 394 patients that 86.4% of the interviewees considered the institution as adequate for cancer diagnosis and treatment during the pandemic, although 27.92% considered that there were delays in the treatment process, interfering with patient satisfaction. 19 …”
Section: Resultsmentioning
confidence: 99%
“…Esses dados estão em consonância com a pesquisa brasileira, conduzida no INCA, no Rio de Janeiro-RJ, que também encontrou maior nível de satisfação com a equipe médica 3 . Entretanto, os dados diferem do estudo realizado em Sanok na Polônia 34 , que tiveram maiores médias nas escalas que avaliaram as habilidades técnicas, interpessoais, informacionais e disponibilidade da equipe de enfermagem.…”
Section: Discussionunclassified
“…On the other hand, researchers were dealing with this issue in the field of selected specialist services. This particularly included studies on access to medical care during pregnancy [25], bariatric care [26], cancer patients care [27], medical and nonmedical services for the elderly [28]. Researchers agree that the COVID-19 pandemic situation leads to a growing problem of limited or complete lack of access to treatment for specific groups of patients who are in need of special care [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers agree that the COVID-19 pandemic situation leads to a growing problem of limited or complete lack of access to treatment for specific groups of patients who are in need of special care [29][30][31]. The perception of medical services during the COVID-19 pandemic was also studied in the context of cancer care [27]. However, no studies on patient satisfaction on the access to primary healthcare and treatment effectiveness in Poland could be found.…”
Section: Introductionmentioning
confidence: 99%